Evoking the Eternal The Royal Ballet dances Ashton, Bintley and MacMillan - Jennings, Luke (Dance Books Ltd., Alton,Hampshire (UK), 2005)
The Royal Ballet dances Ashton, Bintley and MacMillan PALABRAS CLAVE: Royal Ballet, David Bintley, Tombeaux, Frederick Ashton, Enigma Variations, Kenneth MacMillan, Rite of Spring.